Maximum entropy modelling for predicting the potential distribution of wild sesame, Sesamum alatum Thonn. in India: MAXIMUM ENTROPY MODELLING FOR PREDICTING POTENTIAL DISTRIBUTION OF WILD SESAME - B SARATH BABU; NILAMANI DIKSHIT; K RAMEASH; N SIVARAJ (Journal of Oilseeds Research, 2016)
Ecological niche modelling or predictive habitat distribution framework for wild sesame, Sesamum alatum Thonn., an important wild taxa occurring in India has been analyzed using Maximum Entropy method. The model indicated that parts of Kanyakumari, Thoothukudi, Sivaganga, Pudukottai, Coimbatore, Thiruvalluvar districts of Tamil Nadu and Chittoor, Kadapa, Nellore, Prakasam, Guntur, Krishna, West Godavari, East Godavari, Visakhapatnam districts of Andhra Pradesh are falling under high probability regions for climate suitability of S. alatum species where the in-situ conservation and other genetic resources activity could be taken up in the changed climatic regime. Mean temperature of coldest quarter (30.4%), annual mean temperature (26.0%) and mean diurnal range (17.7%) are major bioclimatic variables contributing to the climatic model of the wild sesame.